2005
DOI: 10.1007/s10350-004-0882-7
|View full text |Cite
|
Sign up to set email alerts
|

Small Bowel Obstruction: Conservative vs. Surgical Management

Abstract: Operatively treated patients had a lower frequency of recurrence and a longer time interval to recurrence; however, they also had a longer hospital stay than that of patients treated nonoperatively. There was no significant difference in treatment type or in incidence or type of prior surgery among patients with early and late small bowel obstruction. None of the variables analyzed in this study were significant predictors of the success of a particular treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
122
5
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(143 citation statements)
references
References 19 publications
13
122
5
3
Order By: Relevance
“…There is wide variation in the reported rate of successful nonoperative management among patients with SBO, ranging from 43%-76%. [26][27][28][29][30][31][32][33][34] This likely reflects variation in the etiology of SBO among patients included in previous studies, different clinical thresholds for taking patients with SBO to the operating room and changing practice patterns over the past 3 decades. In the only study that specifically examined treatment of SBO among elderly patients, 19% of patients older than 70 years were treated nonoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is wide variation in the reported rate of successful nonoperative management among patients with SBO, ranging from 43%-76%. [26][27][28][29][30][31][32][33][34] This likely reflects variation in the etiology of SBO among patients included in previous studies, different clinical thresholds for taking patients with SBO to the operating room and changing practice patterns over the past 3 decades. In the only study that specifically examined treatment of SBO among elderly patients, 19% of patients older than 70 years were treated nonoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…35 A downfall of nonoperative management is that it is associated with an increased risk of recurrent SBO compared with surgery. 26,29,34,36 In the largest study of recurrent SBO (n = 32 583), Foster and colleagues 34 reported recurrence after 5 years of follow-up in 20% of patients treated nonoperatively compared with 16% of patients treated surgically. Readmission for recurrence happened earlier in the patients managed nonoperatively than in those managed surgically (median 194 v. 354 d).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, over half will require operative management. 1,2 Moreover, recurrent episodes of adhesive obstruction may occur in 29-42% of patients. 3,4 In addition, the work-load and cost of treating adhesive small bowel obstruction is significant, thus impacting on the resources of a state-funded healthcare service.…”
mentioning
confidence: 99%
“…Appendectomies, gynaecological operations, cholecystectomie, and large bowel cancer resections are supposed to be the commonest surgeries leading to adhesions. [19,20] Operative management was done in 125 patients (61.27%) while 79 patients (38.73%) were conservatively managed. 93% of hernias, 81% of malignancies and 80% of volvulus cases underwent emergency surgeries, while 24% of adhesions were released surgically.…”
Section: Resultsmentioning
confidence: 99%